Optimization of Pulsed Electric Fields-Assisted Extraction of Phenolic Compounds From White Grape Pomace Using Response Surface Methodology - Carpentieri, Serena; Ferrari, Giovanna; Pataro, Gianpiero (Frontiers in Sustainable Food Systems, 2022)
This study was focused on the optimization of the pulsed electric fields (PEF)-assisted extraction process using central composite design for response surface methodology from response surface methodology (RSM) with the aim to sustainably intensify the extractability of phenolic compounds from white grape pomace. The cell disintegration index (Zp) was used as response variable to identify the optimal PEF pre-treatment conditions of grape pomace in terms of field strength (E = 0.5–5 kV/cm) and energy input (WT = 1–20 kJ/kg), to be applied prior to the subsequent solid-liquid extraction (SLE) process. for both untreated and PEF-treated samples SLE process was optimized to determine the most effective combination of extraction temperature (20–50°C), extraction time (30–300 min), and solvent concentration (0–100% ethanol in water). Total phenolic content (TPC), flavonoid content (FC), and antioxidant activity (FRAP) of the obtained extracts were determined. The extracted compounds from untreated and PEF-treated samples at the optimal conditions were analyzed via HPLC-PDA analysis. Results revealed that, at a fixed extraction temperature (50°C), the application of PEF at optimal processing conditions (E = 3.8 kV/cm, WT = 10 kJ/kg) prior to SLE has the potential to reduce the solvent consumption (3–12%) and shorten the extraction time (23–103 min) to obtain the same recovery yield of phenolic compounds. Under optimized conditions, the extracts derived from PEF-treated samples showed significantly higher TPC (8%), FC (31%), and FRAP (36%) values, as compared to the control extraction. HPLC analyses revealed that epicatechin, p-coumaric acid, and quercetin were among the main phenolic compounds extracted, and no degradation phenomena occurred due to PEF application.